Effectiveness Of Criminal Enforcement Against Kreak In Juvenile Justice System Semarang Regency - Winarsih, Laras; Ekaningsih, Lailasari; Alid, Idul Hanzah; Izziyana, Wafda Vivid (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2026)
This study examines the effectiveness of criminal law enforcement against street children associated with the "Kreak" phenomenon in Semarang Regency within the framework of the Juvenile Criminal Justice System (SPPA). The research is grounded in the identified gap between Indonesia's child-centered juvenile justice norms, particularly diversion and restorative justice, and their inconsistent implementation in practice. Using a normative juridical method, this study analyzes primary legal materials, including Law No. 11 of 2012 on the Juvenile Criminal Justice System and Law No. 1 of 2023 on the Criminal Code, supported by relevant legal literature. The findings indicate that law enforcement effectiveness remains limited due to inconsistent diversion practices, weak inter-agency coordination, insufficient rehabilitation and reintegration facilities, and a limited understanding of restorative justice among law enforcement officials. Social stigma and the complex socio-economic background of children further hinder reintegration efforts. This study emphasizes that effectiveness should be measured through rehabilitative outcomes rather than punitive indicators and recommends strengthening restorative justice training, harmonizing SPPA implementation with the Criminal Code, enhancing institutional coordination, and expanding community-based prevention and reintegration programs to ensure child protection and sustainable public safety.